BIODIVERSITY DISCLOSURE IN FINANCIAL ACCOUNTING: A BIBLIOMETRIC OVERVIEW - Arum Kusumaningdyah Adiati; Isnayni Sabila (Faculty of Economics and Business University of Mataram, 2026)
This study was conducted due to the limited number of comprehensive studies on biodiversity disclosure in financial accounting. In fact, this issue is becoming increasingly relevant to sustainability and investor decision-making. This research aims to identify trends, contributions, and gaps in the literature on biodiversity disclosure. The novelty of this study lies in the integration of bibliometric analysis with the identification of conceptual and geographical gaps. The method used a bibliometric analysis of relevant studies indexed in the Scopus database from 2011 to 2025. The analysis was facilitated by RStudio (Biblioshiny). The results indicated an increase in publications after 2020 and a dominance of developed nations, whilst developing countries such as Indonesia remain under-represented. This study contributes by identifying directions for future research, including the development of standardised and integrated biodiversity accounting models, and recommends strengthening disclosure standards in corporate reporting practices.